A Minimalist Theory of Truth. (7th January 2013) - Armour‐Garb, Bradley
Abstract This article, after briefly discussing Alfred Tarski's influential theory of truth, turns to a more recent theory of truth, a deflationary, or minimalist, theory. One of the chief elements of a deflationary, or minimalist, theory of truth is that it replaces the question of what truth is with the question of what "true" does. After setting out the central features of the minimalist theory of truth, the article explains the motivation for opting for such a position. In addition, it provides some reasons for thinking that such a theory of truth is "minimal" or "deflationary" in the way that contemporary truth theorists have claimed it to be.